PENGEMBANGAN E-MODUL BERBASIS SCAFFOLDING UNTUK MENINGKATKAN PEMAHAMAN CERITA FIKSI PADA SISWA KELAS V SEKOLAH DASAR - Desti Dewi Sintya; Anggit Aruwiyantoko; Yurniwati Yurniwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of understanding regarding fictional stories among fifth-grade elementary school students, as well as the limited use of engaging and interactive teaching materials. A needs analysis at SDN Duren Sawit 02 revealed that students still struggled to comprehend the content and intrinsic elements of fictional stories. This study aimed to develop a scaffolding-based e-module to enhance fifth-grade students understanding of fictional stories. The research employed the Research and Development (R&D) method using the ADDIE model. The development process encompassed expert validation, user trials, and an effectiveness test utilizing a one-group pre-test post-test design. The results indicated that the scaffolding-based e-module achieved a feasibility score of 97.70%, placing it in the highly feasible category according to expert validation. Practicality test results showed a score of 92.32% in the limited trial, rising to 97.02% in the field trial; both figures fall into the highly practical category. Effectiveness test results demonstrated an increase in the average student score from 65 on the pre-test to 86 on the post-test, with an N-Gain score of 0.60, falling within the moderate category. Consequently, the developed scaffolding-based e-module is deemed feasible, practical, and effective for improving fifth-grade elementary students understanding of fictional stories.